The rhetorical mediator: understanding agency in Indigenous translation and interpretation through Indigenous approaches to UX - Rivera, Nora K., author; Utah State University Press, publisher (Colorado State University. Libraries, 2024)
Argues that scholars and user experience researchers should include Indigenous technical communicators and their oral practices, specifically interpretation, in disciplinary conversations to raise awareness about Indigenous language rights.--Provided by publisher.
1. Intersecting Theories and Disciplines -- 2. Designing the Research -- 3. Empathizing -- 4. Defining the Issues -- 5. Synthesizing Needs and Issues -- 6. Ideating and Re-Designing.
Text in English and Spanish.
Keywords: Indigenous peoples -- Languages -- Translating -- Research; Communication of technical information -- Research; Translating and interpreting -- Technological innovations -- Research; Linguistic rights -- Research; Indigenous peoples -- Interviews; Translators -- Interviews